Childhood exposure to birth registration laws and old‐age mortality. (29th December 2022) - Noghanibehambari, Hamid; Fletcher, Jason
Abstract: This paper studies the effects of the enactment of birth registration laws, as the official universal and uniform method of recording births, across US states in the first decades of the 20th century on old‐age longevity for children affected by these laws. We show that establishing birth registration laws has long‐term benefits for old‐age health. The benefits are primarily driven by states with an effective child labor policy, suggesting that registering births helps the enforcement of child labor laws which in turn operate as the mechanism channel to improve old‐age longevity. A treatment‐on‐treated calculation suggests an increase of 0.6 years of longevity from not working during childhood due to the birth registration law.